2017
DOI: 10.1063/1.4994974
|View full text |Cite
|
Sign up to set email alerts
|

Blistering mechanisms of atomic-layer-deposited AlN and Al2O3 films

Abstract: Blistering of protective, structural, and functional coatings is a reliability risk pestering films ranging from elemental to ceramic ones. The driving force behind blistering comes from either excess hydrogen at the film-substrate interface or stress-driven buckling. Contrary to the stress-driven mechanism, the hydrogen-initiated one is poorly understood. Recently, it was shown that in the bulk Al-Al2O3 system, the blistering is preceded by the formation of nano-sized cavities on the substrate. The stress- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…By comparing these results, it is observed that the Al 2 O 3 film shows increased negative fixed charge after the heat treatment. Similar results were reported in many papers [19][20][21][22][23]. According to these, the negative fixed charge of Al 2 O 3 results from its structural change.…”
Section: Analysis Of Al 2 O 3 Structuresupporting
confidence: 90%
See 1 more Smart Citation
“…By comparing these results, it is observed that the Al 2 O 3 film shows increased negative fixed charge after the heat treatment. Similar results were reported in many papers [19][20][21][22][23]. According to these, the negative fixed charge of Al 2 O 3 results from its structural change.…”
Section: Analysis Of Al 2 O 3 Structuresupporting
confidence: 90%
“…According to these, the negative fixed charge of Al 2 O 3 results from its structural change. This can be confirmed by the bonding change of Al-O, Al-O-H and Si-O with X-ray photoelectron spectroscopy (XPS) analysis, as well as an analysis of the TEM images [2,4,19,20,24]. We confirmed the structural change of Al 2 O 3 through EELS, showing it has both octahedral and tetrahedral structures.…”
Section: Analysis Of Al 2 O 3 Structuresupporting
confidence: 64%
“…A small tensile stress can be advantageous for membrane applications to keep the membrane flat. A high compressive stress might impose problems such as blistering, 23 which was observed for some samples with longer plasma times.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing H concentration decreases the film density and refractive index 11 and may cause blistering during annealing as has been observed in the case of Al 2 O 3 . 23 Only a few publications exist on the deposition of AlN from AlCl 3 . The thermal deposition of AlN from NH 3 was investigated by Elers et al 24 and Jokinen et al 25 two decades ago and more recently by Lee et al 26,27 using Ar/H 2 / NH 3 plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of the surface quality of several types of material is often due to the formation of blisters [1][2][3][4][5][6]. Blistering is caused by voids inside the material which have reached a sufficient size to touch and deform the surface because of the increased pressure of some gas inside the voids [1][2][3][4][5][6][7][8]. In the worst cases blisters burst leaving craters [1,6,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%